Description of three new species of the genus Cicurina Menge, 1871 from Guangdong, China (Araneae, Hahniidae) - Liao, Rongrong; Yin, Haiqiang; He, Ailan; Xu, Xiang (Zootaxa, 2022)
Three new species of Cicurina Menge, 1871 are described based on specimens collected from Guangdong, China: C. bifurca Liao & Xu, spec. nov. (male), C. spiralis Liao & Xu, spec. nov. (male) and C. tetragongylodes Liao & Xu, spec. nov. (female). Detailed descriptions, photographs, drawings, and a distribution map of the three new species are provided, as well as a phylogenetic tree including the new species.